Efektivitas Kompres Jahe pada Lanjut Usia Penderita Nyeri Osteoarthritis - Flora Rumiati; Gabriel Meistika; Heriyanto Heriyanto; William William (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
Cartilage in the knee of the foot will gradually thin out with age and increase the load on the footstool. The cartilage in the knee is called the meniscus which is useful for protecting the surrounding bones from rubbing against each other when moving. When the meniscus thin and rub against each other will cause pain and the sound of crepitus when walking. Pain is an uncomfortable condition due to physical stimulation that is channeled to the brain followed by physical to emotional reactions. Osteoarthritis is a joint disease that causes decreased joint motion due to pain. This joint disorder most commonly occurs in the knee. Warm ginger compress therapy will make blood vessels widen or open and blood circulation to be smooth. The method of making this literature is in the form of a descriptive approach that looks for various journals or research articles with the same research theme. The results obtained with 10 journals, with the same discussion. Where in several journals get results that are proven to be effective. It can be concluded that warm ginger compresses are effective for reducing pain in osteoarthritis.